Obesidad y sus complicaciones durante la gestación y en el neonato Hospital Regional de Loreto julio a diciembre 2021 - Medina Sevillano, Betty Isabel Mercedes (2022)
Project Title: "Obesity and its complications during pregnancy and in the newborn Hospital Regional de Loreto July to December 2021." General objective: To determine the relationship between obesity and its complications during pregnancy and the newborn at the Regional Hospital of Loreto, between the months of July to December 2021. Methodology: Type of Research Analytical, case-control study. A multivariate logistic regression analysis will be performed to assess the effect of obesity and its complications during pregnancy and in the newborn. Research design: case-control study. The group of obese mothers is the study group while the non-obese group will be the control group. The demographic characteristics, body mass index, gestational weight gain, obstetric history, smoking status, type of delivery, gestational ages, pregnancy complications, and neonatal outcomes of each patient will be recorded. Population and Sample: All obese pregnant women hospitalized in the Department of Gynecology and Obstetrics of the Loreto Regional Hospital, from July to December 2021. For each case (pregnant with obesity) there will be a control (pregnant non-obese). The population is the sample. Data Collection Procedures, Techniques and Instruments: A data collection sheet will be used. Demographic data, clinical characteristics, and its complications will be taken in which it will be studied if they are at risk during pregnancy (among patients with obesity and non-obese). For the descriptive statistics of the total number of patients, the data will be described in medians/medians and measures of dispersion for the quantitative variables. Information processing: The questionnaires will be fed with data from the patients' medical records in Microsoft Excel tables. The data will be stored in a special statistical software for statistical analysis SPSS 25. Multivariable logistic regression analysis will be performed. Protection of human rights: The study is not a clinical trial, medical records will be reviewed to obtain data. Because of this, it is a minimal risk study.